PHYSICAL MAPPING AND INHERITANCE STUDIES OF CRY1AC GENE ON TRANSGENIC COTTON CHROMOSOMES - S. Noreen; Mahmood-ur-Rahman2; T. Husanin (Journal of Animal and Plant Sciences, 2021)
The presence of Bt gene, cry1Ac in transgenic lines of Gossypium hirsutum L. was determined by molecular and cytogenetic analysis. Fluorescence in situ hybridization (FISH) was carried out to study the location of transgene on chromosomes. Metaphase chromosomes prepared from root tips and pollen grains showed more condensation, and hence more karyotypically differentiated. The four transgenic lines of cotton showed stable integration of transgene, cry1Ac. Either the lines were heterozygous (CEMB-3010-14, CEMB-3013-10, CEMB-3016-13 and CEMB-3037-2) or homozygous (CEMB-3034-10) showing single and double genes respectively at interphase and metaphase FISH while the control lines showed no fluorescent signal for transgene at all. Metaphase chromosomes prepared from pollens were also analyzed and single copy of cry1Ac was mapped on chromosome 10 which showed the stable inheritance of transgene in the progeny. The information obtained during the study may be helpful to understand the possible effects of copy number variation and position effect of transgene in Bt cotton. The studies may also help to comprehend the process of transgene inheritance in Bt cotton lines.
Keywords: Karyotyping; Fluorescence in situ hybridization; transgene; cry1Ac; physical mapping